2022
DOI: 10.3389/fmed.2022.851532
|View full text |Cite
|
Sign up to set email alerts
|

B Cells on the Stage of Inflammation in Juvenile Idiopathic Arthritis: Leading or Supporting Actors in Disease Pathogenesis?

Abstract: Juvenile idiopathic arthritis (JIA) is a term that collectively refers to a group of chronic childhood arthritides, which together constitute the most common rheumatic condition in children. The International League of Associations for Rheumatology (ILAR) criteria define seven categories of JIA: oligoarticular, polyarticular rheumatoid factor (RF) negative (RF-), polyarticular RF positive (RF+), systemic, enthesitis-related arthritis, psoriatic arthritis, and undifferentiated arthritis. The ILAR classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 240 publications
(214 reference statements)
1
13
0
Order By: Relevance
“…A restricted number of markers specific to B cells in inflammatory environments were included in this phenotyping panel, limiting comparisons to other studies in inflammatory disease (77). Nevertheless, we were able to confirm reduced B cell numbers in JIA SF (8), additionally displaying SF B cells to be highly activated, in agreement with the hyperactivity of B cells recently suggested as a possible pathogenesis factor of JIA (29, 78).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A restricted number of markers specific to B cells in inflammatory environments were included in this phenotyping panel, limiting comparisons to other studies in inflammatory disease (77). Nevertheless, we were able to confirm reduced B cell numbers in JIA SF (8), additionally displaying SF B cells to be highly activated, in agreement with the hyperactivity of B cells recently suggested as a possible pathogenesis factor of JIA (29, 78).…”
Section: Discussionsupporting
confidence: 89%
“…As we confirmed, B cell frequency in the inflamed joint is dramatically decreased compared to PB (Figure 3A)(8, 10). Despite this, it has been suggested that B cell hyperactivity might contribute to JIA pathogenesis (29). Indeed, B cell cluster 18, which was found almost exclusively in the joint (47.3±5.5% of SF B cells vs 3.1±1.4% of HC PB and 2.7±0.3% of JIA PB B cells, Figure 3D), were characterised by high CD71 expression (Figure 3B-D), a transferrin receptor upregulated on activated lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, although no specific autoantibodies have been described in JIA, a significant fraction of patients displays the presence of antinuclear antibodies (ANA), rheumatoid factor (RF) or anticitrullinated antibodies (ACPA). RF and ACPA are detected in patients with higher risk to develop severe disease and to progress to adult RA [27], while ANA are mainly detected in oligo- and poly-articular JIA, and target several cellular antigens commonly hidden but exposed during apoptotic processes. The pathogenic role of autoantibodies in JIA is still debated, although their presence has been related to the development of ectopic lymphoid structures in synovial tissue [28].…”
Section: T-b Cell Cooperationmentioning
confidence: 99%
“…The affected joint is characterized by hyperplasia, inflammation, and presence of infiltrating immune cells from both the innate and adaptive immune system (4). T-and B-cells are thought to play a role, given the genetic relationship to MHC class II alleles and the presence of ANAs (4)(5)(6). Though, the contribution of members from the innate immune system, such as monocytes, is becoming increasingly recognized (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%